Effectiveness of Ethnomathematics-Based Geometry Learning Using Problem-Based Learning Assisted by Mobile Devices on Students’ Mathematical Disposition - Darojatun Fikri; Hartono (FKIP Universitas Mataram, 2025)
Abstract This article analyses the effectiveness of ethnomathematics-based geometry learning using a Problem-Based Learning (PBL) approach supported by mobile devices on junior high school students’ mathematical disposition. A quantitative approach with a pre-experimental one-group pretest–posttest design was employed in this study. The sample consisted of 30 eighth-grade students selected through a cluster random sampling technique from a public junior high school in Yogyakarta, Indonesia. The instrument used was a mathematical disposition questionnaire comprising 16 validated statements. Data were analysed descriptively and inferentially using the Shapiro–Wilk test, one-sample t-test, and one-population proportion test. The results revealed a significant improvement in students’ mathematical disposition after implementing ethnomathematics-based geometry learning through the PBL approach assisted by mobile devices. The average questionnaire score increased from 48 (poor category) to 59 (good category), with 90% of students achieving or exceeding the good category threshold. These findings indicate that integrating ethnomathematics into problem-solving activities facilitated by mobile technology can foster students’ confidence, persistence, interest, and comfort in discussing and learning mathematics. Keywords:Ethnomathematics; Mobile; Mathematical Disposition; Problem-Based Learning